2017
DOI: 10.2298/tsci151209072u
|View full text |Cite
|
Sign up to set email alerts
|

Experimental investigation of V-gutter flameholders

Abstract: Combustion characteristics and NOx emissions of propane and air mixture in a channel with a bluff body were investigated experimentally. Effects of the angle and type of the flameholder on the NOx emissions, blow-off limit, combustion efficiency, and exhaust gas temperature were examined. The results show that the NOx emissions are dependent on flameholder type and angle. Also it was observed that the perforated V-gutters considerably increases the blow-off performance. Moreover, the blow-off limit decreases a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 11 publications
1
17
0
Order By: Relevance
“…Simulations performed in [15] with a triangular-shaped bluff body (with slits on both sides) and based on experimental data obtained [8] indicate that the increasing in the angle at the corner vertex leads to increased flame stabilization. Similar results have been reported in [16,17].…”
Section: State-of-the-art: a Brief Overviewsupporting
confidence: 91%
See 4 more Smart Citations
“…Simulations performed in [15] with a triangular-shaped bluff body (with slits on both sides) and based on experimental data obtained [8] indicate that the increasing in the angle at the corner vertex leads to increased flame stabilization. Similar results have been reported in [16,17].…”
Section: State-of-the-art: a Brief Overviewsupporting
confidence: 91%
“…It is worth mentioning, see the analysis of Lefebre [31], that this is the most important parameter of flame stabilization. In addition, the preceding study [28] revealed that the most effective way of fuel supply is at the symmetry axis directly to the recirculation zone (i. e. in the inner part of V-gutter). It is important to claim that the further results of this report are related to a rectangular combustion chamber allowing the effect of the boundary layer area to be avoided.…”
Section: Preceding Studies and The New Focus Of The Experimental Programmentioning
confidence: 96%
See 3 more Smart Citations